Analisis SWOT Pada UMKM Seblak Bg (Bang Galih) Dalam Meningkatkan Penjualan dan Daya Saing - Aprilia, Tantri; Yunita, Tyna (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
SWOT analysis is one of several tools available to analyze marketing strategy, as an environmental analysis that takes into account the internal and external factors that influence the company. With the rapid growth of various business fields, including culinary, it provides opportunities for MSME owners, especially in the culinary sector, to be helped by technology to promote their products, one of which is the seblak product which has always been a favorite of the Indonesian people. This research explains the reasons behind product competitiveness and the strategies implemented by Seblak BG (Bang Galih) to increase its sales. This research uses two data collection methods, namely literature review and study observation. From the SWOT matrix analysis table, it can be concluded that MSME Seblak BG has good advantages and opportunities so that it has good competitiveness.